The Irony of Iron – Biogenic Iron Oxides as an Iron Source to the Ocean - Emerson, David (Frontiers in Microbiology, 2016)
Primary productivity in at least a third of the sunlit open ocean is thought to be iron-limited. Primary sources of dissolved iron (dFe) to the ocean are hydrothermal venting, flux from the sediments along continental margins, and airborne dust. This article provides a general review of sources of hydrothermal and sedimentary iron to the ocean, and speculates upon the role that iron-cycling microbes play in controlling iron dynamics from these sources. Special attention is paid to iron-oxidizing bacteria (FeOB) that live by oxidizing iron and producing biogenic iron oxides as waste products. The presence and ubiquity of FeOB both at hydrothermal systems and in sediments is only beginning to be appreciated. The biogenic oxides they produce have unique properties that could contribute significantly to the dynamics of dFe in the ocean. Changes in the physical and chemical characteristics of the ocean due to climate change and ocean acidification will undoubtedly impact the microbial iron cycle. A better understanding of the contemporary role of microbes in the iron cycle will help in predicting how these changes could ultimately influence marine primary productivity.